Of Fungi, Fe, and Filamentation - How Iron Limitation can Bypass the Dfi1 Pathway and Regulate Filamentation - Junier, Ashlee. (Tufts University. Tisch Library., 2022)
Thesis (Ph.D.)--Tufts University, 2022.; Submitted to the Dept. of Genetics.; Advisor: Carol Kumamoto.; Committee: Ralph Isberg, Claire Moore, and Karl Munger.; Keywords: Microbiology, and Genetics.